2009
DOI: 10.1345/aph.1l656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba Extract Ingestion on the Pharmacokinetics of Talinolol in Healthy Chinese Volunteers

Abstract: Our results suggest that long-term use of GBE significantly influenced talinolol disposition in humans, likely by affecting the activity of P-glycoprotein and/or other drug transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 24 publications
2
45
1
2
Order By: Relevance
“…Ginkgo biloba extract and ginkgolides induce the expression of UGT1A1 in human primary hepatocytes, although inhibitory effects on UGT enzymes of ginkgo biloba extract, or one of its components, have been described, as well (16,18,19,29). Other investigations showed that long-term use of ginkgo biloba inhibits P-gp-mediated drug transport, but contrary results have also been reported (1,9,10,30,31).…”
mentioning
confidence: 99%
“…Ginkgo biloba extract and ginkgolides induce the expression of UGT1A1 in human primary hepatocytes, although inhibitory effects on UGT enzymes of ginkgo biloba extract, or one of its components, have been described, as well (16,18,19,29). Other investigations showed that long-term use of ginkgo biloba inhibits P-gp-mediated drug transport, but contrary results have also been reported (1,9,10,30,31).…”
mentioning
confidence: 99%
“…Repeated ingestion of Ginkgo biloba extract by healthy Chinese volunteers was reported to increase talinolol bioavailability significantly without significant changes in elimination halflife and the time to C max (98). These findings suggest that longterm use of Ginkgo biloba extract significantly influences talinolol disposition in humans, most probably by affecting the activity of P-gp and/or other drug transporters.…”
Section: Yeung Et Al (2009) Have Investigated the Effect Of Ethanol mentioning
confidence: 84%
“…Their effects were reported on structure-activity relationships (Gnabre et al, 2010). It is also interesting to note that Schisandra 15 chinensis extract significantly inhibited P-glycoprotein substrate timolol in humans (Fan et al, 2009). This provides further scientific evidence for the adjuvant effect of Schisandra chinensis on cancer therapy.…”
Section: Anti-cancermentioning
confidence: 96%
“…This provides further scientific evidence for the adjuvant effect of Schisandra chinensis on cancer therapy. However, patients receiving the Schisandra chinensis extract may require dose adjustments when treated with drugs primarily transported by P-glycoprotein (Fan et al, 2009). …”
Section: Anti-cancermentioning
confidence: 99%